A Note on Unsuccessful Tender Offers and Stockholder Returns - FABOZZI, FRANK J.; FERRI, MICHAEL G.; FABOZZI, T. DESSA; TUCKER, JULIA (Journal of Finance, 1988)
ABSTRACT Recent research shows that unsuccessful tender offers may affect target share returns for two years past the offer's announcement. This note examines target returns in the interim between the announcement and one year after the offer's withdrawal. Analyzing a recent sample of targets that did not get another bid in the year following a failed tender offer, this study reaches two conclusions. First, all of an offer's premium disappears by the time failure becomes public. Second, excess returns are zero in the post‐failure year. An explanation that is based on the causes of the tender offers' failures is presented.